Rǫgnvaldr Kali Kolsson and Orkneyinga saga [Medieval self-fashioning: Rognvaldr Kali Kolsson and Orkneyinga saga] - Goeres, EM (2015)
This article investigates the process of self-fashioning depicted in the medieval Icelandic text Orkneyinga saga, the 'Saga of the Orkney Islanders'. It argues that the character of Rçgnvaldr Kali Kolsson, Earl of Orkney, is shown to fashion himself in the model of previous Scandinavian rulers as a means of asserting his right to govern, and that the relationship between poetry and prose is key to this process. Through the composition and recitation of verse, the character of Rognvaldr asserts the power to craft his own story and thus to fashion his own identity and that of his subjects. In particular, the article demonstrates that Rognvaldr's expedition to Jerusalem is central to the construction of the earl's story and of his self. It concludes by suggesting that such a depiction of self-fashioning may have been particularly resonant in medieval Iceland, itself a site of hybrid and shifting identities following Norwegian colonisation.